Effect of nanosized bioactive glass addition on some physical properties of biodentine - Mehmet Burak Guneser; Tugce Yuca Ozturk; Asiye Nur Dincer Sahin; Betul Aycan Uysal; Ayce Unverdi Eldeniz (Journal of Applied Biomaterials & Functional Materials, 2023)
The aim of this in vitro study was to investigate some physical properties of Biodentine (BD) (Septodont, France) that has been modified by adding nanosized bioactive glass (nBG) particles to it in different ratios. The cement was modified by adding 1% (7 mg) and 2% (14 mg) nBG powder to BD. BD was used as the control group in its commercial form. A total of 240 cement samples ( n  = 80) were prepared according to the standard measurements for each test. Subsequently, tests to determine compressive strength, microhardness, initial setting time, and solubility of the samples were performed. The obtained data were statistically analyzed using one-way ANOVA and Tukey’s HDS tests, and the significance level was found to be 0.05. The compressive strength values of the samples modified with 1% and 2% nBG were higher than those of the unmodified BD; however, no statistically significant difference was found between them [BD + nBG (2 wt%) ⩾ BD+nBG (1 wt%) ⩾ control BD], ( p  > 0.05). The microhardness values of the samples modified with 1% and 2% nBG were found to be significantly higher than those of the control group [BD + nBG (2 wt%) > BD+nBG (1 wt%) > control BD], p  < 0.05. Initial setting times were determined as 14 min for unmodified BD, 13 min for BD + nBG (1 wt%), and 12 min for BD + nBG (2 wt%). The addition of nBG to BD significantly reduced the initial setting time of BD ( p  < 0.05). A significant decrease was observed in the solubility of the BD modified with nBG samples compared to that of the control group [control BD > BD+nBG (1 wt%) >BD+nBG (2 wt%)], p  < 0.05. Within the limitations of this study, it was found that the addition of certain amounts of nBG to BD positively affected some physical properties of the cement. Future in vitro and in vivo studies should be performed to prove the clinical applicability of the cements used in this study.